Making Sense of Mathematics for Teaching Girls in Grades K - 5 : (Addressing Gender Bias and Stereotypes in Elementary Education) - Adams, Thomasenia Lott; Wenzel, Taylar (Taylar B.), 1981-; Childs, Kristopher (Kristopher J.), 1982-; Neff, Samantha (Samantha R.) (Solution Tree, 2019)
"Making Sense of Mathematics for Teaching Girls: Perceptions, Practices, and Priorities, the latest companion to the Making Sense of Mathematics for Teaching book, highlights the gender achievement gap in mathematics that is present in K-5 classrooms across the United States and uses research to offer readers practical steps to eliminate the inequity. Specifically, readers will examine how their, parents', and school and district leaderships' confidence as a learner of mathematics influences how girls view their ability to learn and retain mathematics knowledge. Authors Thomasenia Lott Adams, Taylar B. Wenzel, Kristopher J. Childs, and Samantha R. Neff offer recommendations to support the teaching and learning of mathematics for girls in the classroom, in the home, and across the district"--